A short episodic history of income distribution in Argentina - Facundo Alvaredo; Guillermo Cruces; Leonardo Gasparini (Latin American Economic Review, 2018)
In this paper, we use tax and household survey data to assess the history of income distribution in Argentina since the beginning of the 20th century. Until the 1970s, the country experienced a fall in inequality in spite of lower income growth. Since then, inequality has generally increased possibly as a result of large-scale shocks such as macroeconomic crises and reform attempts, resulting in a convergence towards traditionally more unequal neighboring countries.
Keywords: N16; D63; O15; D31; D33; 330; Argentine exceptionalism; Argentine history; Inequality; Redistribution